2014
DOI: 10.2196/jmir.3528
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Ambulatory Surgical Follow-Up Visits With Mobile App Home Monitoring: Modeling Cost-Effective Scenarios

Abstract: BackgroundWomen’s College Hospital (WCH) offers specialized surgical procedures, including ambulatory breast reconstruction in post-mastectomy breast cancer patients. Most patients receiving ambulatory surgery have low rates of postoperative events necessitating clinic visits. Increasingly, mobile monitoring and follow-up care is used to overcome the distance patients must travel to receive specialized care at a reduced cost to society. WCH has completed a feasibility study using a mobile app (QoC Health Inc, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 15 publications
2
66
1
2
Order By: Relevance
“…Former studies also claimed communication with doctors was vital for patients' compliance. And digital technology should be applied to supplement interaction with patients [28,29]. Besides the interaction with doctors, a survey of patients with medium and low compliance showed that the worry about the accuracy of their action was another important reason for giving up the system.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies also claimed communication with doctors was vital for patients' compliance. And digital technology should be applied to supplement interaction with patients [28,29]. Besides the interaction with doctors, a survey of patients with medium and low compliance showed that the worry about the accuracy of their action was another important reason for giving up the system.…”
Section: Discussionmentioning
confidence: 99%
“…The patients of chronic pain were able to easily communicate their pain level to the medical doctors and physicians. Armstrong et al (2014) has evaluated the role of mobile application support in improving quality care. The study focused on examining the contribution of mobile homebased apps in reducing the follow up visits of patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thanks to advancements in treatments, BC survivorship is on a steady rise and this cancer is no longer thought of as an acute illness but rather a chronic condition [3,4]. It is common to find mHealth solutions for BC in the scientific literature such as tracking sleep patterns [35], symptoms and treatment side effect management [35][36][37], breast health and wellbeing assessments [38,39], and even comprehensive lifestyle programs with nutrition and physical activity elements [40].…”
Section: Chronic Conditionsmentioning
confidence: 99%